2022
DOI: 10.1111/ejn.15693
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of critical genes and pathways identified a signature of neuropathic pain after spinal cord injury

Abstract: Spinal cord injury (SCI) damages sensory systems, producing chronic neuropathic pain that is resistant to medical treatment. The specific mechanisms underlying SCI-induced neuropathic pain (SCI-NP) remain unclear, and protein biomarkers have not yet been integrated into diagnostic screening. To better understand the host molecular pathways involved in SCI-NP, we used the bioinformatics method, the PubMed database and bioinformatics methods to identify target genes and their associated pathways. We reviewed 250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…In addition, previous studies have also performed bioinformatics analysis of key signaling pathways in SCI (J. H. Li et al., 2020 ). A study proposed by (Z. Li et al., 2022 ) noted that the TLR4/MyD88/NF‐κB inflammatory pathway was activated in SCI through bioinformatics analysis, which further supports our findings. The WGCNA method was used for the construction of a co‐expression network, and modules with clinical features were determined (Tian et al., 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, previous studies have also performed bioinformatics analysis of key signaling pathways in SCI (J. H. Li et al., 2020 ). A study proposed by (Z. Li et al., 2022 ) noted that the TLR4/MyD88/NF‐κB inflammatory pathway was activated in SCI through bioinformatics analysis, which further supports our findings. The WGCNA method was used for the construction of a co‐expression network, and modules with clinical features were determined (Tian et al., 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…The defining characteristic of SCI is the development of cysts, which are closely linked to the TLR/myeloid differentiation primary response gene 88 (MyD88) signaling route in astrocytes. These astrocytes exhibit a persistent apoptotic response to necrosis via the TLR4/Myd88 signaling pathway ( Li et al, 2022 ). The inhibitory effect on axonal regeneration during recovery is typically attributed to the presence of CSPGs that are generated by astrocytes in glial scarring.…”
Section: Pathophysiological Process Of Scimentioning
confidence: 99%
“…Moreover, increased NF-κB activity has been demonstrated not only in the DRGs but also in the spinal cord of various neuropathic pain model animals [21,22,44,182,184,190,191]. Recently, it was also shown that the levels of the pronociceptive factors TNFα and IL-6, which are involved in neuropathic pain development after spinal cord injury, can be decreased by inhibiting the TLR4/MyD88/NF-κB pathway [192]. Similarly, after sciatic nerve injury, the selective inhibition of NF-κB reduces hypersensitivity, which has been shown to be associated with beneficial effects on the levels of the pronociceptive factors IL-6 and iNOS [182].…”
Section: Nf-κb and Neuropathic Painmentioning
confidence: 99%